Formulation and Evaluation of Herbal Gel Containing Kigelia africana(lam.) Benth., Fruits Extract - Bhramaramba, R.; Vardahan Chowdary, M. Harsha; Lova, K. Bharath; Nagarjuna, A. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
Herbal medicine has become an item of global importance both medicinal and economical. Although usage of these herbal medicines has increased, their quality, safety and efficiency are serious concerns in industrialized and developing countries. The present research has been undertaken with the aim to formulate and evaluate the herbal gel containing Kigelia africana(Lam.) Benth., fruits extract. The gel formulation was designed by using Carbapol 940, Kigelia africana(Lam.) Benth., fruits extract, propylene glycol, methyl paraben, propyl paraben and required amount of distilled water. The skin pH (6.8-7.1) was maintained by drop wise addition of Triethanolamine. The physicochemical Parameters of formulations (pH, Spreadibility, Stability etc.) were determined. Stability studies have carried out as per ICH guidelines for 3 months at different temperatures and humidity. The results showed that formulation  ontaining Kigelia africana(Lam.) Benth., fruits extract Show better stability. Further formulations have studied for skin irritation on animal model (Rat) and result showed that there was no skin irritation to animals.